5k+1=4K-11

Simple and best practice solution for 5k+1=4K-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5k+1=4K-11 equation:


Simplifying
5k + 1 = 4K + -11

Reorder the terms:
1 + 5k = 4K + -11

Reorder the terms:
1 + 5k = -11 + 4K

Solving
1 + 5k = -11 + 4K

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 5k = -11 + -1 + 4K

Combine like terms: 1 + -1 = 0
0 + 5k = -11 + -1 + 4K
5k = -11 + -1 + 4K

Combine like terms: -11 + -1 = -12
5k = -12 + 4K

Divide each side by '5'.
k = -2.4 + 0.8K

Simplifying
k = -2.4 + 0.8K

See similar equations:

| -2+2x=-(4-3x) | | 12(7m+2)=6(4m-7) | | -2(n-1)=10-n | | 20f+14=13f+35 | | 3(5x-3)=51 | | 3G-6g(g-8)=42 | | 4x+5-3=5x-3x+12 | | 4x+1-6x+3+2= | | -6a-34=-5(1+7a) | | 4(r-3)=2(r+8) | | 3x-5=9x-17 | | q=11200-100p-1960 | | 3a+2=a+7 | | -2Ax^2+2Ax+2A-2Bx+b-2C=x^2 | | 27-w=14 | | x=15*90 | | 2s+2=134 | | 6x+9x-22=66-7 | | 5(3x-9)-8=5(x-3)+32 | | (2x-5)(2x-4)=0 | | q=9240-100p | | F(1)=2x-4 | | 10p^2-13p+5=0 | | -4.7v-44.2=-8.3v | | v=523.6*.75 | | 2x-18=-x+24 | | 5x+4x=-9 | | 12-9y-45=-1+y | | -3(8-8x)=-3(x+8) | | v=523.6*(3/4) | | 3(8-2x)=-3+3x | | z^2-11z-12=0 |

Equations solver categories